Collaborative Governance through Public Service Malls in Barru Regency: Assessment, Initiation, Deliberation, and Implementation - Irwan Alim; Ahmad Taufik; Nurfaidah Nurdin (Mengeja Indonesia Publisher, 2022)
This study investigates Collaborative Governance through Public Service Malls in Barru Regency using a qualitative, descriptive approach. Primary and secondary data sources from five informants were collected through observation, interviews, and documentation techniques, with data validity ensured using triangulation techniques. The research reveals that the Assessment phase aligns stakeholders' objectives, with the Barru Regency DPMPTSP trusted to facilitate other agencies' integration into the Public Service Mall (MPP) to realize excellent service. In the Initiation phase, the primary organizing resource is the Barru Regency DPMPTSP, while the MPP's funding sources are charged to the APBD. The Deliberation phase has been effective, demonstrating a commitment to cooperation articulated in a Memorandum of Understanding. The Implementation phase of the Public Service Mall in Barru Regency has been successful overall, as it facilitates both licensing and non-licensing services for the local community.